A Study on the Influencing Factors and Policy Implications of Low Fertility Intentions among Female College Students in Sichuan Province - Luo, Feifan; Zhou, Shixi (Journal of Social Science and Humanities, 2025)
Drawing on theories of gender equality and reflexive modernization, this study analyzes the author’s previous research on female university students in Sichuan Province, delving into the factors influencing this group’s low fertility intentions and proposing policy optimization pathways. The study found that female university students’ fertility intentions are constrained by multiple factors, including high fertility costs under social pressure, a gap between social support and the needs of women of childbearing age, and the limited incentive effect of the three-child policy. Through a review and reflection on Sichuan Province’s current fertility policy, the study identifies shortcomings in aligning incentives with group desires, the degree to which fertility costs are socialized, and the alleviation of role tensions for women. Therefore, this study proposes recommendations for clarifying the underlying policy logic, strengthening targeted research and adjustments, and prioritizing women’s agency and rights. These recommendations provide insights for enhancing women’s fertility intentions, optimizing local fertility support policies, and promoting social development.